Dr. Franc Pediček in plesna kultura Slovencev - Zagorc, Meta (Šport (Ljubljana), 2013)
In his third book, Views of physical education, sport and recreation, Dr. Franc Pediček dedicated more than 80 pages to dance which means that this activity was of great interest in him, from the perspective of both the engagement of young people and its integration into social and particularly school currents. He started exploring the meaning of dance when he studied the spare time of young people and particularly the different leisure activities they engaged in at the time. Many of his arguments from the end of the 1960s are still valid today.
Keywords: anthropology; antropologija; dance; education; pedagogika; pedagogy; Pediček, Franc, 1922-2008; physical culture; ples; sport; šport; telesna kultura